Novel High-Speed Elongation Rheometer - Bier, Alexander; Arne, Walter; Schubert, Dirk W. (Macromolecular Materials and Engineering, 2022)
The elongational viscosity of polymers can be determined by utilizing different devices such as extensional rheometer after Sentmanat (SER), oil bath rheometer after Meissner or tensile rheometer after Munstedt (MTR), with strain rates up to 10 s(-1). Although these investigations are already complex, they do not depict real fiber spinning processes where higher elongation strain rates occur. Therefore, a novel method is developed to calculate the elongational viscosity of polymers during the fiber spinning process. To reduce the complexity of the system, two polymethylmethacrylates (PMMAs) with different molar masses are investigated using a capillary rheometer to exclude crystallization effects. The diameter of the polymeric strand is determined via a high-speed camera from the die exit to the aspirator. In addition, simulations are carried out to describe the temperature profile of the polymeric strand along the spinline. It is possible to determine the elongational viscosity of the polymers in dependence of temperature and strain rates up to 100 s(-1), by calibration of the force in an aerodynamic stretching device (aspirator).
CRIS-Team WoS Importer:2022-04-29